Role of Adjuvant Therapy for Stage IA Serous and Clear Cell Uterine Cancer: Is Observation a Valid Strategy?. Issue 3 (March 2016) - Velker, Vikram; D'Souza, David; Prefontaine, Michel; McGee, Jacob; Leung, Eric
Abstract : Objectives: The adjuvant treatment of early stage IA serous and clear cell carcinomas of the uterus is controversial. The aims of the study were to report on a single institution experience treating these high-risk early uterine cancers and to identify women who may be suitable for observation alone. Methods and Materials: A retrospective review of patients presenting from 2003 to 2013 with pathologic stage IA (International Federation of Gynecology and Obstetrics 2009) serous or clear cell uterine carcinoma was performed. Patient and disease characteristics, surgical staging, treatment details, and recurrence data were collected. Recurrence rates and 5-year actuarial estimates of recurrence free survival (RFS) were the primary outcomes of interest. Results: A total of 77 patients with stage IA were identified. Median (range) follow-up was 34 (1–108) months. Staging lymphadenectomy was performed in 83%. Adjuvant treatment was given to 27 patients, whereas 50 underwent observation. There were 12 recurrences total, with the 5-year RFS 79% for the cohort, with no statistically significant difference between observation and adjuvant treatment. Only 4 patients received adjuvant chemotherapy and none recurred. In the observation cohort, the presence versus absence of myometrial invasion showed a trend to poorer 5-year RFS (75% vs 93%, P = 0.06). Conclusions: Observation seems to be a valid strategy in those patients with stage IA serous and clear cell carcinoma without myometrial invasion. The presence of any myometrial invasion may confer a higher risk of recurrence, although further studies are needed to determine the optimal adjuvant treatment regimen.